Aspirin Use Is Associated With Decreased Mechanical Ventilation, Intensive Care Unit Admission, and In-Hospital Mortality in Hospitalized Patients With Coronavirus Disease 2019. (21st October 2020) - Chow, Jonathan H.; Khanna, Ashish K.; Kethireddy, Shravan; Yamane, David; Levine, Andrea; Jackson, Amanda M.; McCurdy, Michael T.; Tabatabai, Ali; Kumar, Gagan; Park, Paul; Benjenk, Ivy; Menaker, Jay; et al.
Abstract : BACKGROUND: Coronavirus disease-2019 (COVID-19) is associated with hypercoagulability and increased thrombotic risk in critically ill patients. To our knowledge, no studies have evaluated whether aspirin use is associated with reduced risk of mechanical ventilation, intensive care unit (ICU) admission, and in-hospital mortality. METHODS: A retrospective, observational cohort study of adult patients admitted with COVID-19 to multiple hospitals in the United States between March 2020 and July 2020 was performed. The primary outcome was the need for mechanical ventilation. Secondary outcomes were ICU admission and in-hospital mortality. Adjusted hazard ratios (HRs) for study outcomes were calculated using Cox-proportional hazards models after adjustment for the effects of demographics and comorbid conditions. RESULTS: Four hundred twelve patients were included in the study. Three hundred fourteen patients (76.3%) did not receive aspirin, while 98 patients (23.7%) received aspirin within 24 hours of admission or 7 days before admission. Aspirin use had a crude association with less mechanical ventilation (35.7% aspirin versus 48.4% nonaspirin, P = .03) and ICU admission (38.8% aspirin versus 51.0% nonaspirin, P = .04), but no crude association with in-hospital mortality (26.5% aspirin versus 23.2% nonaspirin, P = .51). After adjusting for 8 confounding variables, aspirin use was independently associated with decreased risk of mechanical ventilation (adjusted HR, 0.56, 95% confidence interval [CI], 0.37-0.85, P = .007), ICU admission (adjusted HR, 0.57, 95% CI, 0.38-0.85, P = .005), and in-hospital mortality (adjusted HR, 0.53, 95% CI, 0.31-0.90, P = .02). There were no differences in major bleeding ( P = .69) or overt thrombosis ( P = .82) between aspirin users and nonaspirin users. CONCLUSIONS: Aspirin use may be associated with improved outcomes in hospitalized COVID-19 patients. However, a sufficiently powered randomized controlled trial is needed to assess whether a causal relationship exists between aspirin use and reduced lung injury and mortality in COVID-19 patients.